Properties and strains of additional DNA repair-defective mutants in known and new genes of Neurospora crassa. - E. Käfer; D. Luk (Fungal Genetics Reports, 1988)
Some time ago, a number of mutants hypersensitive to MMS (methyl methane-sulfonate) were induced in Neurospora to obtain further types of DNA repair-deficient mutants; e.g., rec^- types not yet identified in Neurospora (meiotic-defective mutants generally are "hyperrec"; Schroeder 1986 Curr. Genet. 10:381-387).